ESL Learners Learning Content Subject in English : What do the Malaysian First Cohort Students Say? - Chuah, Kee Man; Soubakeavathi, Rethinasamy; Mohd. Hafizan, Hashim (Common Ground Publishing, 2012)
Throughout the world English language has become an important language of academic instruction. Thus, the teaching and learning of a contentsubject in English is not a unique phenomenon in various parts of the world. In Malaysia, English for the Teaching of Mathematics and Science (ETeMS) policy was implemented in 2003. This has received and is still receiving various reactions particularly from politicians, parents, language experts and policy makers. This study employed a survey research design and investigated the views of the 600 students who have completed all 6 years of primary education under the ETeMS policy. Four aspects of the students’ views namely, views on personal ability in English, learning Science in English, importance of learning Science in English and language medium preference were covered in the questionnaire items. The findings show that the majority of the students viewed their English language ability as good, had positive views about learning Science in English, very aware of the importance of learning Science in English and preferred to learn Science in English only and bilingually in the Malay language and English. The paper highlights the need to listen to the students’ voice and recommends the way forward for addressing English medium instruction issues.